Identification Of Markers For Serodiagnosis Of Leptospirosis In Malaysia - Riazi,, Mehdi (2012)
Leptospirosis is one of the emerging diseases of both humans and animals worldwide, particularly in the tropics. It is a major public health problem due to the lack of diagnostic facilities for early detection which is key in preventing serious multi-organ complications. Although culture and microscopic agglutination test (MAT) are gold standard, they require time and expertise and are not useful for early diagnosis. Thus this study was performed to identify antigenic components of Leptospira for sensitive and specific serodiagnosis of the disease.